2016
DOI: 10.1186/s13099-016-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

The novel norovirus genotype GII.17 is the predominant strain in diarrheal patients in Shanghai, China

Abstract: In the winter of 2014–2015, a novel norovirus (NoV) strain (GII.17) was reported to be the major cause of gastroenteritis outbreaks in East Asia. To determine the time course of gastroenteritis infections associated with the GII.17 strain and whether GII.17 was the main epidemic strain in diarrheal patients in Shanghai, 2169 stool samples were collected and tested. The detection rate of NoV GI and GII NoV strains was 0.83 and 24.02%, respectively. Phylogenetic analysis confirmed that there were seven NoV genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A phylogenetic tree was constructed with 139 sequences from the strains collected and 24 additional worldwide reference sequences. The nucleotide sequences of the NoV ORF2 gene revealed that the GII.17 strains tended to cluster more with the strain Hu/JP/2014/GII.P17_GII.17/Kawasaki323 than with the strain Hu/US/2002/GII.17/CSE1, which suggested that the Kawasaki323 strain became the novel prevalent strain in Shanghai [ 17 ]. In the GII.4 group, the strain Hu/AU/2012/GII.4/Sydney/NSW0514 was more frequently observed than Hu/JP/2005/GII.4/Sakai was, indicating that the Sydney strain was still the predominant GII.4 strain in Shanghai (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic tree was constructed with 139 sequences from the strains collected and 24 additional worldwide reference sequences. The nucleotide sequences of the NoV ORF2 gene revealed that the GII.17 strains tended to cluster more with the strain Hu/JP/2014/GII.P17_GII.17/Kawasaki323 than with the strain Hu/US/2002/GII.17/CSE1, which suggested that the Kawasaki323 strain became the novel prevalent strain in Shanghai [ 17 ]. In the GII.4 group, the strain Hu/AU/2012/GII.4/Sydney/NSW0514 was more frequently observed than Hu/JP/2005/GII.4/Sakai was, indicating that the Sydney strain was still the predominant GII.4 strain in Shanghai (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Noroviruses are genetically diverse and can be divided into seven genogroups (GI-GVII) that are further subdivided into numerous genotypes [ 7 ]. The GII genotype 4 (GII.4) includes most epidemic and pandemic strains, while GII.17 was recently attributed with major outbreaks in East Asia [ 8 ]. Norovirus illness is typically self-limiting and usually subsides in several days.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between NoV detection rates in boys and girls was compared using a two-sided chisquare test in SPSS Statistics v. 19.0 (IBM Corp., Armonk, NY, USA), and a P-value less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Shanghai mainly adopted either ORF1 or ORF2 nomenclature to understand the epidemiology of NoVs in children under five years of age [18][19][20][21][22]. Here, we adopted a dual nomenclature system based on both ORF1 and ORF2 to investigate the diversity of NoV GII genotypes in children suffering from acute gastroenteritis who visited the Children's Hospital of Fudan University in Shanghai from January 2012 to December 2017.…”
Section: Introductionmentioning
confidence: 99%